STUDI KLAYAKAN BISNIS : ASPEK EKONOMI DAN SOSIAL (Studi Kasus: GO-JEK) - Nabila Iskandar; Anisah Cyntia Dewi Pratama (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the business feasibility of GO-JEK as a pioneer of online transportation services in Indonesia, with a focus on socio-economic impacts, economic challenges, and government support. This study uses a qualitative method with a literature study approach, utilizing relevant academic literature published in the last 10 years. The results of the analysis show that GO-JEK has a significant positive impact on the national economy, such as job creation, increasing MSME income, and empowering certain groups. However, challenges such as partner income and competition with the traditional sector need to be addressed. Continued government support is key to the development of the GO-JEK business model to provide inclusive and sustainable socio-economic impacts.